2018
DOI: 10.1039/c8cc03384f
|View full text |Cite|
|
Sign up to set email alerts
|

Development of glycosynthases with broad glycan specificity for the efficient glyco-remodeling of antibodies

Abstract: The first systematic investigation of the effect of high mannose, hybrid, and bi- and tri-antennary complex type glycans on the effector functions of antibodies was achieved by the discovery of novel Endo-S2 mutants generated by site-directed mutagenesis as glycosynthases with broad substrate specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…Since our results demonstrated significant statistical interaction between core fucosylation and terminal galactosylation, and are in strong agreement with previous studies utilizing mAbs with highly homogeneous glycoforms, [37][38][39]42 we hypothesize that the interpretation of results could be compromised when evaluating mixtures of different types of glycoform. Our evaluations of the effects of terminal sialylation in FcγRIIIa binding analysis by SPR and ADCC reporter bioassay using N-glycosylated ligand agree with previous reports that have described reduction of FcγRIIIa affinity, 13,38,40,46,49,50 but found no evidence of an unchanged affinity as previously reported. 30,34,51,52 For terminally sialylated glycoforms and terminally mannosylated mAb-HM, results regarding FcγRIIIa shown in SPR and ADCC reporter bioassay were significantly different from affinity chromatography analysis.…”
Section: Effector Functions and Affinity Characteristics To Fc Receptorssupporting
confidence: 92%
“…Since our results demonstrated significant statistical interaction between core fucosylation and terminal galactosylation, and are in strong agreement with previous studies utilizing mAbs with highly homogeneous glycoforms, [37][38][39]42 we hypothesize that the interpretation of results could be compromised when evaluating mixtures of different types of glycoform. Our evaluations of the effects of terminal sialylation in FcγRIIIa binding analysis by SPR and ADCC reporter bioassay using N-glycosylated ligand agree with previous reports that have described reduction of FcγRIIIa affinity, 13,38,40,46,49,50 but found no evidence of an unchanged affinity as previously reported. 30,34,51,52 For terminally sialylated glycoforms and terminally mannosylated mAb-HM, results regarding FcγRIIIa shown in SPR and ADCC reporter bioassay were significantly different from affinity chromatography analysis.…”
Section: Effector Functions and Affinity Characteristics To Fc Receptorssupporting
confidence: 92%
“…Several research groups have correlated this effect to a reduced affinity for FcγRIIIa; others associated sialylation to increased conformation flexibility of the IgG Fc, which would in turn favour binding to DC-SIGN [ 14 , 53 ]. However, the effects of sialylation are still debated, with others showing that α2,6-sialylation has no significant influence on the IgG-FcγRIIIa interactions (compared to terminal galactosylation) and that the observed anti-inflammatory activity was independent of sialylation [ 46 , 54 , 55 , 56 , 57 ]. On the other hand, terminal galactosylation increases the affinity between IgG and FcγRIIIa [ 14 , 27 , 46 , 54 , 56 ].…”
Section: Igg-fcγr Interactionmentioning
confidence: 99%
“…Finally, the use of endoglycosidases being specific to the whole glycan tree rather than only one residue was also explored. In this approach, an endoglycosidase is able to remove the N-glycans of a protein while another endoglycosidase transfers a new already-assembled glycan [ 53 , 55 , 56 , 88 ]. However, these in vitro engineering approaches remain expensive, long, and poorly scalable as of today [ 54 ].…”
Section: Toward a Better Understanding Of The Igg-fcγr Interactionmentioning
confidence: 99%
“…Moreover, Shivatare et al found that the T138Q mutant of Endo-S2 also reduced hydrolytic activity, though it maintained transglycosylation activity, and generated antibodies with new glycoforms of various high-mannose, hybrid and complex type oligosaccharides. 48) A residue in the proximity of the catalytic domain like Thr-138 might also modulate the glycosynthase activity. These results stimulated further studies on the remodeling of whole bodies of therapeutic mAbs and analyses of their biofunctions.…”
Section: Use Of Transglycosylation Activity Of Endoglycosidases For Igg Remodelingmentioning
confidence: 99%